Development and validation of risk prediction equations to estimate survival in patients with colorectal cancer: cohort study - Hippisley-Cox, Julia; Coupland, Carol (BMJ Publishing Group, 2017)
Objective: To develop and externally validate risk prediction equations to estimate absolute and conditional survival in patients with colorectal cancer.